Comprehensive overview: efficacy, tolerability, and cost-effectiveness of clobazam in Lennox–Gastaut syndrome - Faulkner MA (Dove Medical Press, 2015)
Michele A Faulkner1,21Department of Pharmacy Practice, Creighton University School of Pharmacy, 2Department of Neurology, Creighton University School of Medicine, Omaha, NE, USAAbstract: Clobazam is the newest medication approved by the US Food and Drug Administration (FDA) for the treatment of Lennox–Gastaut syndrome (LGS) in patients at least 2 years of age, although the medication has been available in countries around the world to treat epilepsy and anxiety disorders for many years. Though classified as a benzodiazepine, the drug differs structurally from other drugs in the class as it possesses nitrogen atoms at the 1 and 5 positions within the heterocyclic ring rather than at the 1 and 4 positions. This difference and the classification of clobazam as a partial agonist are believed to be responsible for the decreased incidence of sedative effects compared to other benzodiazepines. Adverse events associated with clobazam use in clinical trials have generally been mild to moderate in nature. Data from an open-label extension trial have confirmed that clobazam is efficacious for the treatment of seizures associated with LGS, particularly atonic seizures (drop seizures), over the long term. Tolerance to the drug’s antiepileptic effects does not seem to be a common occurrence. The drug has proven to be a cost-effective option for therapy, particularly due to its ability to decrease the number of seizures that require medical treatment. Clobazam represents a welcome addition to the treatment options for LGS.Keywords: clobazam, Lennox–Gastaut syndrome, drop seizures